2003
DOI: 10.1007/pl00021512
|View full text |Cite
|
Sign up to set email alerts
|

Forest Floor Decomposition Following Hurricane Litter Inputs in Several Puerto Rican Forests

Abstract: Hurricanes affect ecosystem processes by altering resource availability and heterogeneity, but the spatial and temporal signatures of these events on biomass and nutrient cycling processes are not well understood. We examined mass and nutrient inputs of hurricane-derived litter in six tropical forests spanning three life zones in northeastern Puerto Rico after the passage of Hurricane Georges. We then followed the decomposition of forest floor mass and nutrient dynamics over 1 year in the three forests that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 47 publications
3
134
1
3
Order By: Relevance
“…In previous studies, litterfall accumulation was shown to decrease solar radiation on mineral soil surface, together with reduced forest transpiration in the trimmed plots, causing soil to retain more moisture [14,50,51]. However, during our study, soil moisture did not differ significantly between the control and CTDD plots until the 12th week after treatment.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In previous studies, litterfall accumulation was shown to decrease solar radiation on mineral soil surface, together with reduced forest transpiration in the trimmed plots, causing soil to retain more moisture [14,50,51]. However, during our study, soil moisture did not differ significantly between the control and CTDD plots until the 12th week after treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…After Hurricane Hugo crossed Puerto Rico in September 1989, it took 60 months for the total litterfall (fallen leaves and fine wood) to return to the pre-hurricane level in a tabonuco forest of the Bisley Experimental Watersheds [49]. After Hurricane George defoliated the tabonuco forest in Puerto Rico in September 1998, total forest floor mass and fallen leaves continually decreased to below pre-hurricane levels during the first year [50]. In our study, total floor mass in the CTDD plots continually decreased after the CTDD treatment in December 2014, with elevated floor mass lasting for only 65 weeks, after which it fell below litter standing stocks in the control plots.…”
Section: Discussionmentioning
confidence: 99%
“…500 g m À2 fine litter and ca. 250 g m À2 wood in the Bisley section of the LEF; Ostertag et al, 2003) than after Hurricane Hugo or in the CTE.…”
Section: Microclimatic Attributes (Light Moisture Debris)mentioning
confidence: 92%
“…Forest floor litter mass in tabonuco forest nearly doubled after Hurricane Hugo (based on litter depth; Guzmán-Grajales and Walker, 1991), after Hurricane Georges (Ostertag et al, 2003), and after the debris addition treatments in the CTE (based on litter Shiels et al, 2010), the majority of the litter mass on the forest floor after Hurricane Georges was leaf material (50-60%) rather than wood (30-40%; Ostertag et al, 2003). Fine litter (leaves + twigs and palm fronds) that was deposited on the forest floor debris addition plots of the CTE (1989 ± 26 g m À2 ; Shiels et al, 2010) was nearly identical to that in the same section of the LEF following Hurricane Hugo (1934 ± 26 g m À2 , debris suspended and deposited on the ground; Lodge et al, 1991); yet the amount of wood deposited into each debris addition plot within the CTE was slightly greater (4020 ± 139 g m À2 ; Shiels et al, 2010) than that deposited by Hurricane Hugo in the same section of the LEF (ca.…”
Section: Microclimatic Attributes (Light Moisture Debris)mentioning
confidence: 99%
See 1 more Smart Citation